A Thick Translation of Hmong Oral Epics from the Perspective of Cultural Anthropology - Fei Wu (Randwick International of Social Science Journal, 2022)
Hmong Oral Epics is an oral classic of the Miao people, carrying the cultural memory of the ancient history of the Miao people. The Hmong Oral Epics translated by American sinologist Mark Bender has been praised as "a classic version of transnational cooperation" by scholars. The success of this translation depends on what the translators used flexibly thick translation strategies from the perspective of cultural anthropology, thus making it a good example of the successful application of thick translation to translating national classics. This paper first expounds the theory and feasibility of thick translation of cultural classics from the perspective of cultural anthropology, and then reveals the secret of the success of Mark Bender's translation of Hmong Oral Epics from three aspects, namely the English translation process of Hmong Oral Epics, ethnography orientation, and the translators' comprehensive use of various forms of thick translation both inside and outside translation, with an attempt to promote more Chinese ethnic minority cultural classics to better go to the world.